Prenatal diagnosis of Aicardi syndrome based on a suggestive imaging pattern: A multicenter case‐series. (10th January 2022) - Pomar, Léo; Ochoa, José; Cabet, Sara; Huisman, Thierry A. G. M.; Paladini, Dario; Klaritsch, Philipp; Galmiche, Aurore; Prayer, Florian; Gacio, Sebastián; Haratz, Karina; Malinger, Gustavo; Van Mieghem, Tim; et al.
Abstract: Objectives: To characterize a suggestive prenatal imaging pattern of Aicardi syndrome using ultrasound and MR imaging. Methods: Based on a retrospective international series of Aicardi syndrome cases from tertiary centers encountered over a 20‐year period (2000–2020), we investigated the frequencies of the imaging features in order to characterize an imaging pattern highly suggestive of the diagnosis. Results: Among 20 cases included, arachnoid cysts associated with a distortion of the interhemispheric fissure were constantly encountered associated with complete or partial agenesis of the corpus callosum (19/20, 95%). This triad in the presence of other CNS disorganization, such as polymicrogyria (16/17, 94%), heterotopias (15/17, 88%), ventriculomegaly (14/20, 70%), cerebral asymmetry [14/20, 70%]) and less frequently extra‐CNS anomaly (ocular anomalies [7/11, 64%], costal/vertebral segmentation defect [4/20, 20%]) represent a highly suggestive pattern of Aicardi syndrome in a female patient. Conclusion: Despite absence of genetic test to confirm prenatal diagnosis of AS, this combination of CNS and extra‐CNS fetal findings allows delineation of a characteristic imaging pattern of AS, especially when facing dysgenesis of the corpus callosum. Key points: What is already known about this topic? Aicardi syndrome (AS) is a rare developmental encephalopathy, characterized by the classic triad of infantile spasms, agenesis of the corpus callosum, and chorioretinal lacunae As the genetic etiology of AS is unknown and its classic triad cannot be extrapolated to prenatal diagnosis, to establish a prenatal imaging pattern is of major interest What does this study add? We confirmed and completed a prenatal imaging pattern highly suggestive of AS, based on the most frequent features encountered in a large series: arachnoid cysts associated with a distortion of the interhemispheric fissure, agenesis of the corpus callosum, cortical malformations and heterotopias, and less frequently extra‐CNS anomaly (ocular anomalies, costal/vertebral segmentation defect)